ZAMONAVIY TA’LIMDA CHET TILLARINI O‘RGANISHNING INNOVATSION USULLARI - Usmonova Sayidaxon,; Matkarimova Ashurxon, (TADQIQOTLAR, 2025)
ABSTRACT:  Modern  education  in  language  learning  is  enriched  with innovative approaches, enhancing efficiency through digital pedagogy and interactive methods. Online learning platforms expand opportunities for remote education, while AI-based language learning ensures a personalized approach for each learner. These technologies  contribute  to  making  the  language  learning  process  more  convenient, effective, and faster, ultimately improving the quality of education. Innovative methods help strengthen students' practical skills and increase their level of comprehension. Additionally,  these  approaches  make  language  learning  a  more  engaging  and interactive experience.